The Effectiveness of Digital Service Transformation on Public Satisfaction at The Kedondong Village office in Cirebon Regency - Afnan Adiyanti; Yanto Heryanto (Riviera Publishing, 2026)
Digital transformation in public services has become an essential requirement for village governments seeking to improve the quality of services provided to communities. The Kedondong Village Government in Cirebon Regency has initiated the implementation of digital-based services to improve efficiency, transparency, and accessibility. However, the effectiveness of this digital transformation and its impact on community satisfaction require further investigation. This study aims to examine the effectiveness of digital transformation in public services and its impact on community satisfaction at the Kedondong Village Office. This research employed a qualitative approach using descriptive methods. Data were collected through observations, in-depth interviews with village officials and residents, and document analysis. The findings indicate that the digital transformation of village services improved service speed, accessibility, and administrative transparency. However, the effectiveness of implementation remained constrained by challenges, including limited digital literacy among residents and inadequate technological infrastructure. Overall, digital transformation had a positive impact on community satisfaction, particularly in terms of service timeliness and convenience. This study recommends strengthening the digital competencies of village officials and providing digital literacy programs for the community to optimize the implementation of digital-based public services.